The importance of making the accused understand the nature and consequences of pleading guilty - Abdul Rani Kamarudin, (Fakulti Undang - Undang, 2005)

(untitled)
The purpose of the charge in a criminal trial proceeding is to give to the accused person sufficient information of the allegation made against him so that he may then defend the allegation to his level best. Having said that, having the charge alone is not enough; the court is required to have it explained to the accused and to make sure that the accused understands it the way it should be legally understood. Not only that, an accused must be made aware too by the court the nature and consequences of entering a plea of guilt or claiming trial. How are these explanations to be done? This paper attempts to clarify the matter in the light of the provision in the Malaysian Criminal Procedure Code (hereinafter referred to as the ‘Criminal Procedure Code’ or the ‘CPC’, the Syariah Criminal Procedure (State of Selangor) Enactment 2003 (hereinafter referred to as the ‘Selangor Criminal Procedure’ or the ‘SCP’) and decided cases